The Association Knowledge and Community Practice with the Incidence of DHF (Study in the Village of Putat Jaya Surabaya on 2010–2014) - Rahmawati Sari Budi Utami (Universitas Airlangga, 2015)
Dengue Hemorrhagic Fever (DHF) is still one of the problems to date in Indonesia. Incident Rate (IR) and Case Fatality Rate (CFR) are indicators of DHF events. The purpose of the study was to identify and analyze the relationship between knowledge and actions of the community with the incidence of DHF in Putat Jaya Village, Surabaya in 2010-2014. This study uses a cross-sectional design. Interviews were conducted on 397 people spread over 15 Hamlet in Putat Jaya Village, Surabaya. Subjects were drawn from the population by simple random sampling. The dependent variable is the DHF event. The independent variable is people's knowledge and actions. Data analysis using the Chi-Square test. The results showed that respondents who had suffered from DHF were mostly> 40 years old (56.7%), had a senior high school/equivalent education (47.5%), and were a housewife (62.3%). Most respondents have good knowledge (82.3%) and pretty good action (50%). Community knowledge was not related to the incidence of DHF (p=0.206). Community actions related to the incidence of DHF (p=0.009). The conclusion of the research is that community actions have a relationship with the incidence of DHF. The Health Department is advised to work together across sectors, disseminating dengue fever through electronic media, regular training of earth cadres, increasing community participation through dengue mosquito source reduction (PSN), and distributing anti-mosquito lotions for free to the public.